A CASE STUDY ON REDUCTION OF LUNG FUNCTIONS IN PATIENTS WITH DIABETES MELLITUS IN ANDHRA PRADESH, INDIA - Suranjan, Bantupalli; Deekshit, Atluri; S, Bala Yaswanth Kumar; Teja, Gutha Bala (Universal Journal of Pharmaceutical Research, 2021)
Background and Objectives: The purpose of this study is to evaluate the pulmonary functions in patients with diabetes. Many studies additionally counsel that the respiratory organ as an organ in diabetes and glycemic exposure could also be an effort issue for reduced respiratory organ operate. Systemic inflammation, hypoxemia, oxidative stress, altered gas exchange, and changes in lung tissues were the major impacts on the respiratory system which were induced by hypoglycemia. Methods: Forty individual patients of both sexes were involved in the study and divided into two groups depending on their conditions. Group A consists of individuals without any complications or any disease conditions and group B consists of diabetic patients excluding smokers and divided into twenty to each group. Results: SPSS software was used for the analysis and spirometry was the device used to determine the pulmonary function. Values of Forced Expiratory Volume 1, Forced Vital Capacity, Forced Expiratory Flow, FEV% were only considered in the study and the study results conclude that diabetes shows its effect on the lungs in long term and leads to a decrease in lung function. Conclusion: It was concluded that that monitoring the Pulmonary function tests of the diabetic patients helps the individuals to avoid any complications further ahead and also it helps to ease the flow of the recovery and also prevent further more comorbidity that might arise in the future. Peer Review History: Received: 6 August 2021; Revised: 8 September; Accepted: 11 October; Available online: 15 November 2021 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. Kolawole Oyetunji Timothy, Department of Pharmacology and Therapeutics, Ladoke Akintola University of Technology, Ogbomoso, Nigeria. otkolawole@lautech.edu.ng Dr. Nuray Arı, Ankara University, Turkiye, ari@ankara.edu.tr Dr. Rima Benatoui, Laboratory of Applied Neuroendocrinology, Department of Biology, Faculty of Science, Badji Mokhtar University Annaba, BP12 E L Hadjar–Algeria, benattouiryma@gmail.com